2022
DOI: 10.3389/fcimb.2022.1061125
|View full text |Cite
|
Sign up to set email alerts
|

Differential microbiota network in gingival tissues between periodontitis and periodontitis with diabetes

Abstract: Periodontitis and diabetes mellitus (DM) have a bidirectional relationship. Periodontitis is initiated by dysbiosis of oral microorganisms, and in particular, the characteristics of the microorganisms that have penetrated the tissue are directly related to the disease; therefore, we investigated the effect of DM on intragingival microbial profiling of patients with periodontitis. A total of 39 subjects were recruited and divided into three groups in this case control study as follows: healthy (NA, 10), periodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Another study, which compared healthy controls both to periodontal disease patients and to diabetic patients with periodontal disease, showed that patients with periodontal disease had higher numbers of perio-pathogens (mostly pathogenic from the red group), but patients with diabetes and periodontal disease had higher numbers of periodontal pathogens which connected with other pathogens (orange group). Although no major diversity was found within the phyla of the pathogens, the authors suggested that the connection between the periodontal pathogens is the cause for the rapid progression of periodontal disease in diabetic patients [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study, which compared healthy controls both to periodontal disease patients and to diabetic patients with periodontal disease, showed that patients with periodontal disease had higher numbers of perio-pathogens (mostly pathogenic from the red group), but patients with diabetes and periodontal disease had higher numbers of periodontal pathogens which connected with other pathogens (orange group). Although no major diversity was found within the phyla of the pathogens, the authors suggested that the connection between the periodontal pathogens is the cause for the rapid progression of periodontal disease in diabetic patients [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Secretory Ig A makes up two-thirds of the Ig A class antibodies of the human body and causes opsonization and agglutination of microorganisms, has a bacteriostatic effect, prevents the adhesion of microorganisms to the epithelium, and neutralizes bacterial toxins [18,19,20,21]. The higher concentrations of Ig A observed in diabetic patients may be the result of an immune response to advanced glycation end products, which increase and accumulate due to persistently high blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia leads to inflammatory response disturbances ( 42 ), enhancing pro-inflammatory cytokines and matrix metalloproteinases (MMP) expression ( 35 ), so the periodontal tissue metabolism adversely affects blood vessels and promotes periodontitis, which develops more rapidly and more intensely ( 43 ), with hyperglycemia enhancing its progression ( 44 , 45 ), even at pre-DM levels ( 46 ). Importantly, hyperglycemia severity, not the DM diagnosis, affects the periodontium ( 47 , 48 ).…”
Section: Periodontal Diseasesmentioning
confidence: 99%